2023
DOI: 10.3389/fpls.2023.1152875
|View full text |Cite
|
Sign up to set email alerts
|

Non-rhizobial nodule endophytes improve nodulation, change root exudation pattern and promote the growth of lentil, for prospective application in fallow soil

Abstract: Non-rhizobial endophytes (NREs) are active colonizers inhabiting the root nodules. Though their active role in the lentil agroecosystem is not well defined, here we observed that these NREs might promote the growth of lentils, modulate rhizospheric community structure and could be used as promising organisms for optimal use of rice fallow soil. NREs from root nodules of lentils were isolated and examined for plant growth-promoting traits, exopolysaccharide (EPS) and biofilm production, root metabolites, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 140 publications
0
4
0
Order By: Relevance
“…As previously evidenced, phytohormone production, AHL, ACC deaminase, nitrogen fixation, P and Zn solubilization, and biofilm formation play crucial roles in stimulating plant growth under normal conditions through the activity of Serratia spp. strains ( Martínez et al, 2018 ; Hakim et al, 2021 ; Debnath et al, 2023 ).…”
Section: Serratia Spp Strains As Plant Growth-promoting Bact...mentioning
confidence: 99%
“…As previously evidenced, phytohormone production, AHL, ACC deaminase, nitrogen fixation, P and Zn solubilization, and biofilm formation play crucial roles in stimulating plant growth under normal conditions through the activity of Serratia spp. strains ( Martínez et al, 2018 ; Hakim et al, 2021 ; Debnath et al, 2023 ).…”
Section: Serratia Spp Strains As Plant Growth-promoting Bact...mentioning
confidence: 99%
“…Moreover, studies at the field level have focused on leveraging nodule endophytes to enhance the growth and adaptation of legumes to degraded estuarine soils. They have demonstrated that non-rhizobial nodule endophytes exhibit a significant potential to improve nodulation, modulate root exudation patterns, and foster legume growth ( Dhole and Shelat, 2022 ; Debnath et al, 2023 ).…”
Section: Main Properties Of Nodule Endophytesmentioning
confidence: 99%
“…Studies have documented the nitrogen-fixing capabilities of Serratia sp., Herbaspirillum sp., Paenibacillus sp., Arthrobacter sp., Klebsiella sp., Pseudomonas sp., Bacillus sp., Bosea sp., and Enterobacter sp. strains isolated from legume nodules ( Valverde, 2003 ; Muresu et al, 2008 ; Selvakumar et al, 2008 ; Ibáñez et al, 2009 ; Knežević et al, 2021 ; Debnath et al, 2023 ).…”
Section: Main Properties Of Nodule Endophytesmentioning
confidence: 99%
See 1 more Smart Citation